THE ROLE OF FAMILY IN IMPROVING THE QUALITY OF HUMAN RESOURCES - Udi Iswadi (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Improving the quality of human resources is one of the important keys in the development of a country. Quality human resources can increase productivity, creativity, and innovation, so as to encourage better economic growth. One of the factors that affect the quality of human resources is the role of the family. This study aims to examine the role of the family in improving the quality of human resources. The focus of this research is qualitative. Methods for gathering information include paying close attention and making detailed notes, with subsequent analysis including data reduction, visualization, and inference. The results of the study arrived at the conclusion that the role of family is very important in improving the quality of human resources. Families can provide positive education and support for children, form strong character, and create anenvironment conducive to child development.